Occupational exposure to work-related stress, a proposal of a pilot study to detect psychological distress in collarworkers - Borelli, I.; Rossi, M. F.; Santoro, P. E.; Gualano, M. R.; Tannorella, B. C.; Perrotta, A.; Moscato, U. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Work-related psychosocial risks have been identified as significant occupational health and safety risks; the occupational physicians must assess and monitor the health status of workers in order to verify that work is not a source of harm to exposed operators. The aim of the study was to investigate the outcomes related to anxiety and depression traits in workers exposed to stress-related work. Methods. A questionnaire was administered to a large population of Italian public administration workers; the Centre for Epidemiologic Studies - Depression Scale questionnaire was used to measure depression, the Self rating Anxiety Scale was used to measure anxiety, the UK Management Standards Indicator tool questionnaire was used to assess work adjustment. A descriptive analysis, a multivariate analysis, as well as logistic regression models were used to assess the health outcomes related to stress. Results. A total of 292 workers participated in the study; 100% of participants had a Centre for Epidemiologic Studies - Depression Scale score over the cut-off; 41.78% had a Self rating Anxiety Scale score over the cut-off; the results support a correlation between the Centre for Epidemiologic Studies - Depression Scale results and the UK Management Standards Indicator tool results; and a correlation between Self-rating Anxiety Scale results and the UK Management Standards Indicator tool results. Conclusions. The Demand, Management, Support and Relationship results were associated with mental health outcomes, and it could be a useful tool in occupational medicine, to identify workers at risk for negative mental health outcomes, becoming an essential tool in workers’ health assessment and for prevention of mental health disorders.